A new adaptive traffic engineering method for telesurgery using ACO algorithm over Software Defined Networks - Parsaei, M.R.; Mohammadi, R.; Javidan, R. (European Research in Telemedicine / La Recherche Européenne en Télémédecine, 2017)
In the past decades, telemedicine has attracted much attention due to its usefulness for delivering medical services from remote location. One of the most important parts of telemedicine is telesurgery, in which a surgeon performs surgery on the patient from remote location by using telecommunication networks. Due to the surgeon needs to watch the patient side transmitted video with high quality; it is necessary to provide fast and suitable communication path between the surgeon and patient. Emerging Software Defined Network (SDN) as a new network paradigm facilitated Quality of Service (QoS) provisioning in many applications. Decoupling data plane from control plane in SDN, helps to manage based on end users requirements. This paper proposes a new heuristic traffic engineering method for telesurgery application using Ant Colony Optimization (ACO) algorithm. This paper models QoS provisioning in Telesurgery as a Constraint Shortest Path (CSP) linear programming problem. Moreover, due to NP-completeness of CSP problem, this paper proposes a solver method using ACO algorithm. To the best of our knowledge, this is the first paper which investigates QoS provisioning for telesurgery in SDN. Results of performance evaluation showed that the proposed method is better than baseline method. The proposed method improves all three important QoS parameters, average End-to-End delay, packet loss ratio and PSNR with values of 56.3%, 50.5% and 1.33, respectively. providing QoS in telesurgery applications is one of the most challenging issues. By leveraging the capability of SDN, we can develop appropriate mechanisms to guarantee QoS requirements in critical applications such as Telesurgery. Using SDN together with optimization models such as CSP for providing QoS in Telesurgery can improve the quality of the received video in an operation room. This mechanism causes increment in the performance of Telesurgery. Au cours des dernières décennies, pour l’accés aux services médicaux dans les régions éloignées, la télémédecine est hautement considérée. L’une des parties les plus importantes de la télémédecine, c’est la chirurgie à distance, qui s’effectue par un chirurgien via des réseaux informatiques dans un endroit éloigné du patient. Pendant l’opération, le chirurgien a besoin d’une vidéo de haute qualité et d’accomplir cela nécessite une infrastructure de communication rapide et pratique entre le chirurgien et le patient. Les réseaux base de logiciels (SDN), en tant qu’une nouvelle architecture pour fournir une qualité de service, ont été mis en place dans des diverses applications. En SDN, la séparation du niveau de donné du niveau de gestion, en fonction des besoins des utilisateurs aide à mieux gérer. Cet article présente une nouvelle méthode d’ingénierie de trafic pour l’application de la chirurgie distance en utilisant l’algorithme méta-heuristique ACO. Dans cet article, la qualité de service requis pour la chirurgie à distance est considérée comme un modèle de programmation linéaire de CSP. Puisque le problème CSP est des problèmes NP, dans cet article, l’algorithme ACO est utilisé pour le résoudre. Les résultats de l’évaluation des performances montrent que la méthode proposée est mieux que la base. L’approche proposée a amélioré respectivement tous les trois paramètres de moyenne du délai, pourcentage de la perte de paquets et PSNR en quantité de 56,3 %, 50,5 % et 1,33 %. Fournir la qualité de service des applications de chirurgie à distance, est l’une des questions les plus importantes. En utilisant les capacités de SDN, nous pouvons créer un mécanisme qui garantit les exigences de qualité de service dans les applications critiques telles que la chirurgie à distance. L’utilisation simultanée de SDN et des modèles d’optimisation tels que le CSP pour fournir un service de qualité en chirurgie à distance peut améliorer la qualité de la vidéo de la salle d’opération. Ce mécanisme augmente la performance de la chirurgie à distance.